Respuesta :
5x-y=-6
y=-7x+6
The second equation tells you what Y is, so replace y in the first equation with its value:
5x- (-7x+6) = -6
Remove the parenthesis:
5x + 7x +6 = -6
Simplify:
12x + 6 = -6
Add 6 to both sides:
12x = 0
Divide both sides by 12:
x = 0
Now you have x, replace x with 0 and solve for y:
5(0) -y = -6
0 - y = -6
Multiply both sides by -1:
y = 6
The solution is X = 0 and y = 6, which is written as (0,6)
Answer:
5x-y=-6.............1
y=-7x+6...........2
substituting value of y in equation 1
5x-(-7x+6)=-6
5x+7x-6=-6
12x=0
x=0/12=0
substituting value of x in equation 1
5×0-y=-6
y=6